Preliminary validation of a brief PROM assessing psychological distress in patients with malignant mesothelioma: The mesothelioma psychological distress tool—Patients - Guglielmucci, Fanny; Bonafede, Michela; Azzolina, Danila; Marinaccio, Alessandro; Franzoi, Isabella Giulia; Migliore, Enrica; Mensi, Carolina; Chellini, Elisabetta; Romeo, Elisa; Grosso, Federica; Granieri, Antonella (Frontiers in Psychology, 2022)
Abstract Objective: Psychological suffering in malignant mesothelioma (MM) differs from that in other cancers because of its occupational etiology, and we aimed to develop specific patient-reported outcome measures (PROMs) to assess it. Methods: We used a multi-method prospective observational multicentric study (N=149), and a preliminary questionnaire validation was performed through a Bayesian approach.. Results: Item analysis showed a good internal consistency and reliability (Cronbach alpha = 0.79 [95% CI=0.74-0.93]. Twenty of the 41 initial items were selected as posterior 95% highest density interval (HDI) factor loading standardized effect size fell outside of the region of practical equivalence (ROPE). Bayesian exploratory factor analysis (BEFA) showed a two-factor structure: 1) Trauma-related reactions (TR, 13 items) and 2) Claim for justice (CJ, 7 items), confirmed by the Bayesian confirmatory factor analysis (BCFA). Latent factors were poorly correlated (Posterior median: 0.13; 95% CI=-0.079–0.323). The 90% root mean square error of approximation (RMSEA) posterior median was 0.04 [90% CI = 0.03–0.58]; the 90% Chi-square posterior median was 242 [90% CI = 209–287]. Conclusions: Psychological suffering in MM patients implies negative cognitive, emotional, and somatic reactions related to the traumatic impact of the disease and the need to obtain justice through economic compensation. Our findings provide preliminary evidence that the Mesothelioma Psychological Distress Tool-Patients (MPDT-P) could be a promising and reliable instrument to assess MM patients’ psychological distress.